Optical coherence tomography for patch test grading: A prospective study on its use for noninvasive diagnosis of allergic contact dermatitis. (21st October 2020) - Ruini, Cristel; Rahimi, Farnaz; Fiocco, Zeno; French, Lars E.; Hartmann, Daniela; Oppel, Eva; Sattler, Elke
Abstract: Background: The diagnosis of allergic contact dermatitis should be confirmed by skin patch tests. Distinguishing between irritant and allergic reactions is sometimes difficult. Objectives: To analyse the in vivo morphological changes in patch test reactions compared to healthy skin, and to detect subclinical changes in doubtful reactions using optical coherence tomography (OCT). To develop an OCT‐based algorithm to support patch‐test grading. Methods: One hundred twenty‐nine skin patch‐test areas were scanned with OCT to evaluate the following features: architectural and vascular morphology, epidermal thickness, optical attenuation coefficient (AC), and blood flow at 0.1, 0.2, and 0.35 mm depth. Results: Most common OCT features of acute contact allergic reactions in patch tests were spongiosis with microvesicles (94.8%), macrovesicles (60.3%), and coalescing vesicles (46.6%), the latter useful in differentiating acute allergic from irritant dermatitis ( P‐ value < .05). Objective quantitative parameters correlated well with the severity grade: epidermal thickness due to spongiosis, AC ( P‐ value < .05) and blood flow at 0.2 and 0.35 mm ( P‐ value < .01). Conclusions: OCT as a noninvasive diagnostic tool, established for skin cancer diagnosis, is useful for evaluating contact allergic patch‐test reactions. Not only morphological but also objective features such as blood flow and AC correlate with the reaction severity. Further studies are needed to explore the differences in irritant and allergic contact dermatitis. Abstract : OCT: optical coherence tomography OCT as a noninvasive diagnostic tool, established for skin cancer diagnosis, is useful for evaluating contact allergic patch‐test reactions. OCT and dynamic OCT visualize morphological features such as spongiosis and vesiculation, as well as objective features such as blood flow and attenuation coefficient. The above‐mentioned features correlate patch‐test reaction severity and can be used to support the clinical grading of patch tests.